2012
DOI: 10.30638/eemj.2012.254
|View full text |Cite
|
Sign up to set email alerts
|

Water Monitoring Following the Hungarian Red Mud Disaster

Abstract: The wall of the red mud waste disposal facility at Ajka, Hungary ruptured on October 4, 2010. Nearly about 1 million m 3 of red mud sludge got out of the disposal facility and the neighbouring environment was heavily contaminated. In the emergency situation the top priority was put on the rescue of human lives and to provide first aid to the injured people. Many people end their lives will wear the scars caused by the caustic red mud sludge. The polluted surface waters (Stream Torna, River Marcal and River Ráb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Mayes et al (2011) reported rapid contaminant dilution, with the exception of depositional hotspots, in the river system affected by the Ajka accident, indicating species-specific transport rates through the system (Mayes et al, 2011). Although chemical recovery was reported to be rapid, good ecological condition in the Torna Stream polluted in the Hungarian accident is not expected to be achieved until 2021, some 11 years after the pollution event (Kovács et al, 2012). Our results indicate that chemical recovery time may be significantly longer in depositional zones with long hydraulic retention times.…”
Section: Recovery Following Red Mud Pollutionmentioning
confidence: 99%
“…Mayes et al (2011) reported rapid contaminant dilution, with the exception of depositional hotspots, in the river system affected by the Ajka accident, indicating species-specific transport rates through the system (Mayes et al, 2011). Although chemical recovery was reported to be rapid, good ecological condition in the Torna Stream polluted in the Hungarian accident is not expected to be achieved until 2021, some 11 years after the pollution event (Kovács et al, 2012). Our results indicate that chemical recovery time may be significantly longer in depositional zones with long hydraulic retention times.…”
Section: Recovery Following Red Mud Pollutionmentioning
confidence: 99%
“…23 Longer term measures included channel dredging and the removal of red mud from affected oodplain areas. Extensive monitoring by regulatory agencies was also carried out in the year aer the disaster 24,25 while routine biological monitoring suggested wildlife recovered in the affected systems according to government press releases. 22 Recent studies based on ambient water quality monitoring data have however highlighted the persistence of As and Ni in high concentrations in the water column in the two years aer the disaster.…”
Section: Introductionmentioning
confidence: 99%